Pengembangan Sistem Informasi Penjadwalan Pelayan Ibadah pada Gereja Mawar Sharon Malang Menggunakan Metode Waterfall - Bella Nemesias Prasetiyani; Niken Hendrakusma Wardani; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mawar Sharon Church Malang organizes Sunday service activities every Sunday by involving several church servants from several service departments. One service department that plays an important role in the successfulness of Sunday is the Multimedia Department. The Multimedia Department carries out services according to the service schedule made by the coordinator every month. The service schedule is still created manually via group chat and Microsoft Excel. This manual scheduling can take one to two hours, and the resulting schedule often conflicts. The purpose of this study is to provide solutions to problems by developing information systems for scheduling worship services. The scheduling system was developed by the waterfall method and applies genetic algorithms to produce an optimal schedule. Scheduling system that has been made is then tested with black box testing and the result is that the system has run well according to its function. The results of the parameter testing are obtained a population of 90, generation 40, crossover rate 0.4 and mutation 0.6 which produces the best schedule. User testing results on performance criteria which show that the scheduling system is able to cut the scheduling time to 91%, the reliability criteria indicate that the system is able to make an appropriate service schedule and there are no conflicts, and for usability criteria a value of 94% is obtained (strongly agree) from church servants and 90% (strongly agree) from the coordinator which means the system is easy to use.